1975
DOI: 10.1111/j.1469-1809.1975.tb00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of ACP1 and MNSs in families with structural rearrangements involving chromosome 2

Abstract: Data from seven families carrying rearrangements and variants of chromosome 2 have been analysed in relation to the assignment of ACP1 and MNSs. The data are consistent with the regional assignment of ACP1 to 2p23, but not with that of MNSs to band 2q14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
3
7
0
Order By: Relevance
“…Since the patient, monosomic for part of 2q, is a heterozygote at the red cell acid phosphatase (ACP1) and MNS loci, these loci cannot be in the chromosome region 2q31->2qter, substantiating previous reports (Mace et al, 1975). The data, combined with linkage information from other families, have been presented elsewhere (Higgins et al, 1975).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Since the patient, monosomic for part of 2q, is a heterozygote at the red cell acid phosphatase (ACP1) and MNS loci, these loci cannot be in the chromosome region 2q31->2qter, substantiating previous reports (Mace et al, 1975). The data, combined with linkage information from other families, have been presented elsewhere (Higgins et al, 1975).…”
Section: Discussionsupporting
confidence: 75%
“…Human Biochemical Genetics Unit. As the assignment of ACP1 and MNSs to chromosome 2 has been suggested (Mace et al, 1975) particular attention was paid to these markers, which are shown in Fig. 4.…”
Section: Genetic Marker Studiesmentioning
confidence: 99%
“…There was also a 45% reduction in acid phosphatase activity. This assignment is consistent with the segregation of acid phosphatase in seven families with structural rearrangements involving chromosome 2 (2). Using spontaneous chromosome rearrangements in human-Chinese hamster somatic cell hybrids, Hamerton et al (3) have recently localized the erythrocyte acid phosphatase gene to the p23 band of chromosome 2.…”
supporting
confidence: 59%
“…Regional assignment of ACPl was established by Ferguson-Smith et al (1973) who demonstrated a gene dosage effect in a patient with a deletion of 2p from 21323 -2pter. Several authors have since supported this assignment (Povey et al 1974, Chu et al 1975, Mace et al 1975, Magenis et al 1975, Snows & Brown 1975, Higgins et al 1976). Hamerton et al (1975), using somatic cell hybrid techniques, further proposed the ACPl locus as band 2p23, and this was confirmed by Emanuel et al (1979).…”
mentioning
confidence: 87%